Daily and seasonal frequency of Cupressus sempervirens in relation to atmospheric conditions (Damascus University Journal of agriculture sciences, 2026)
Aerobiology aims to monitor the atmospheric load of airborne pollen and fungal spores, especially those that cause allergies or on diseases humans, animals and plant, as well as the effect of weather factors on aerosols concentrations in the atmosphere and their vertical and horizontal transport. This study aimed to monitor the daily and seasonal changes of Cupressus sempervirens pollen in the air and its link to the main weather factors (precipitation, temperature, wind speed). A portable device, invented and implemented for this purpose, was installed at 1.5 m above ground level. Sampling was conducted five times a day at (9, 11.14.17.20 h). The results indicate that cypress pollen concentration was generally higher 2019. Pollen liberation season extended from February until the end of March and then decreased during April and May until complete, absence for the rest of the year. The actual season duration was 49 days in 2018 with a peak at the first half of March. While in the second season of 2019, the pollen liberation period was 65-days with a peak from February 25 to the first half of March. A strong relationship was observed between pollen concentration and climate factors. The effect was positive for high temperatures that helped mature open and male cones and pollen release, while rainfall had the opposite effect, as the number of pollen grains decreased during and after rainy days, where the lowest recorded values were reached. Wind speed played a positive role in augmenting the pollen grains and liberation, and dispersion
Keywords: Spore Trap; Pollen Liberation; Weather Conditions